A Case Study of Puerperal Group A Streptococcal Infection Complicated by Toxic Shock Syndrome - Robert J. Olp; Ingrid A. Chamales; Stacey S. Schmiedecke (Thieme Medical Publishers, Inc., 2020)
Puerperal infection with group A streptococcus (GAS), Streptococcus pyogenes, is associated significant morbidity and mortality. When associated with toxic shock syndrome (TSS), mortality rates rise to approximately 50%. We present the case of a 32-year-old Para 2 reporting severe left distal lower extremity pain, fevers, and chills at 1 week following an uncomplicated vaginal delivery. The patient's clinical status rapidly decompensated to septic shock requiring transfer to the intensive care unit. She underwent anterior and lateral compartment fasciotomy of the left lower extremity for concerns of possible necrotizing soft tissue infection. Final blood cultures confirmed GAS infection with unclear primary source, though endometritis was favored. She required additional orthopaedic procedures including an arthroscopy with washout for contralateral septic arthritis and myositis before her discharge on hospital day 19. She obtained a near-full recovery complicated by poor wound healing and permanent left foot drop. While GAS remains a rare puerperal event, obstetricians should recall there is a 20-fold increased incidence among postpartum women. Progression to TSS is associated with very poor prognosis and hysterectomy is often necessary. Favorable outcomes in GAS with or without TTS hinge on astute clinical suspicion, aggressive fluid resuscitation, early antibiotic therapy, and source control.